Recommended Road Maintenance Strategy for the Wareng–Mukus Road in Pacitan Regency Based on the Analytical Hierarchy Process (AHP) and the Provincial/Kabupaten Road Management System (PKRMS) - Wahyu Kusuma Wardhana; Hanie Teki Tjendani; Esti Wulandari (Enrichment: Journal of Multidisciplinary Research and Development, 2026)
Road infrastructure plays a crucial role in supporting regional connectivity, economic activity, and public services. However, limited maintenance budgets require local governments to establish effective road maintenance priorities based on both pavement condition and the strategic importance of road networks. This study aims to determine the recommended maintenance strategy for the Wareng–Mukus Road Section in Pacitan Regency by integrating the Analytical Hierarchy Process (AHP) and the Provincial/Kabupaten Road Management System (PKRMS). AHP was used to determine the relative importance of decision criteria through pairwise comparisons with expert respondents, while PKRMS was used to evaluate pavement condition based on engineering indicators the Surface Distress Index (SDI) and Trafficability Index (TTI) and to identify appropriate maintenance alternatives. The results show that road condition is the most influential criterion (weight 34.27%), followed by traffic volume (23.63%), connectivity (15.65%), economic and agricultural corridor function (12.04%), access to public service facilities (7.70%), and regional development (6.71%). Based on the integrated AHP–PKRMS analysis, periodic preventive maintenance emerged as the most appropriate strategy, with the highest priority value of 57.00%, followed by minor rehabilitation (25.51%) and routine maintenance (17.50%). This recommendation aligns with the existing pavement condition, classified as serviceable fair according to TTI and good according to SDI. The integration of AHP and PKRMS provides a systematic, objective decision-making framework that supports evidence-based maintenance planning, optimizes resource allocation, and enhances the sustainability of road asset management.